The Effect of Perceived Value, Customer Satisfaction, and Switching Cost on Customer Loyalty - Sudirjo, Frans; Panjaitan, Feliks Anggia Binsar Kristian (West Science Business and Management, 2025)
This study examines the effects of Perceived Value, Customer Satisfaction, and Switching Costs on Customer Loyalty using a quantitative approach with 150 respondents. Data were collected using a Likert scale (1–5) and analyzed using Structural Equation Modeling - Partial Least Squares (SEM-PLS). The findings reveal that all three constructs significantly influence customer loyalty, with perceived value having the strongest impact. Customer satisfaction and switching costs also demonstrate positive and significant relationships with loyalty, highlighting their critical roles. The study concludes that enhancing perceived value, ensuring customer satisfaction, and increasing switching costs collectively strengthen customer loyalty. Practical implications for businesses include strategies to enhance value perception, address customer satisfaction, and create switching barriers. These findings contribute to understanding loyalty formation and offer actionable insights for improving customer retention.